Curves for days - Moher, Laura (Sourcebooks Casablanca, an imprint of Sourcebooks, 2023)
"Sexy Southern romance with a charming plus-size heroine and a gruff, grumpy hero. Rose Barnes feels best when she's invisible--so when she wins the lottery and is suddenly thrust into the spotlight where everyone wants something, hiding out in a small town in North Carolina makes perfect sense. Rose has got curves for days--and to Angus, the big, burly, bearded contractor working on her new house, she's just plum perfect. Rose is surprised to learn that Angus has a sense of humor and a soft heart beneath that gruff exterior. Angus can't help noticing that wacky Rose is smart, funny, and has a sexy underwear stash that leads him to some very unprofessional fantasies. As their unlikely friendship becomes love, Angus becomes determined to help Rose overcome what he believes are financial troubles. But with Angus's need to always give more than he receives, Rose's multi-million secrets could mean the end of a beautiful relationship"--